Uncover the Indonesia Middlepowermanship: When Indonesia find the Middle Power Moment? - Bima Jon Nanda (Frequency of International Relations (FETRIAN), 2023)
Indonesia is middle power state. But no state can be a middle power all the time. There is middle power moment which allows ones to pursue its middle powerdom. This article aim to explain Indonesia middlepowermanship and its middle power moment. This article applies a data-driven, qualitative approach using secondary data. This article argues that Indonesia middlepowermanship is Indonesia’s persistent effort to build a rules-based regional order in Southeast Asia and the broader Indo-Pacific using ASEAN and Bali Democracy Forum. While Indonesia middle power moment started as early of 2003, when Indonesia take the role as ASEAN chairmanship that lead into Bali Concord II and ASEAN Charted 2008.